Assessment of Pediatric Cancer and Its Relationship to Environmental Contaminants: An Ecological Study in Idaho. (12th March 2022) - Joseph, Naveen; Kolok, Alan S.
Abstract: The primary aim of this study was to determine the degree to which a multivariable principal component model based on several potentially carcinogenic metals and pesticides could explain the county‐level pediatric cancer rates across Idaho. We contend that human exposure to environmental contaminants is one of the reasons for increased pediatric cancer incidence in the United States. Although several studies have been conducted to determine the relationship between environmental contaminants and carcinogenesis among children, research gaps exist in developing a meaningful association between them. For this study, pediatric cancer data was provided by the Cancer Data Registry of Idaho, concentrations of metals and metalloids in groundwater were collected from the Idaho Department of Water Resources, and pesticide use data were collected from the United States Geological Survey. Most environmental variables were significantly intercorrelated at an adjusted P ‐value <0.01 (97 out of 153 comparisons). Hence, a principal component analysis was employed to summarize those variables to a smaller number of components. An environmental burden index (EBI) was constructed using these principal components, which categorized the environmental burden profiles of counties into low, medium, and high. EBI was significantly associated with pediatric cancer incidence ( P ‐value <0.05). The rate ratio of high EBI profile to low EBI profile for pediatric cancer incidence was estimated as 1.196, with lower and upper confidence intervals of 1.061 and 1.348, respectively. A model was also developed in the study using EBI to estimate the county‐level pediatric cancer incidence in Idaho (Nash‐Sutcliffe Efficiency = 0.97). Plain Language Summary: Previous studies focused on human exposure to environmental contaminants and their potential associations to cancer incidence among children. However, most do not consider how several environmental pollutants may act together, potentially leading to human health outcomes. The study aimed to understand how several environmental contaminants, such as agricultural pesticides, metals, etc., together are associated with cancer incidence among children. The Cancer Data Registry of Idaho provided the data on cancer incidence among children, information on metals was provided by the Idaho Department of Water Resources, and pesticides from the United States Geographical Survey. This study developed a new measure of Environmental Burden for each county in Idaho. The study identified that the counties with high Environmental Burden were more closely associated with cancer incidence among children than counties with low Environmental Burden. Key Points: This study analyzed the relationships of pediatric cancer rates to an aggregate of several potentially carcinogenic metals and pesticides An environmental burden index (EBI) was constructed and categorized the environmental profiles of counties in Idaho as low, medium, and high A statistical model was developed using the EBI to estimate pediatric cancer incidence in Idaho